"I'm in their shoes": Experiences of peer educators in sexuality and relationship education. Issue Volume 39:Issue2(2014) (3rd April 2014) - Frawley, Patsie; Bigby, Christine
Abstract: Background Sexuality and relationship education for adults with an intellectual disability has failed to include them in roles other than as learners. This paper reports findings from a study of the experiences of peer educators with an intellectual disability who co-facilitated a respectful relationships education program. Method Qualitative data were collected about the experiences of 16 peer educators through in-depth interviews and observations of their work in delivering the program. These data were thematically analysed. Findings Peer educators reported that peer education gave them a sense of empowerment, positioned them as credible sources of information about relationships, enabled them to help others, and gave them an opportunity to learn new knowledge about respectful relationships, community resources and supports, and new skills. Conclusions This study presents an alternative approach to relationship education that involves people with an intellectual disability as peer educators and that benefits these people.